Cortical Lewy bodies and Aβ burden are associated with prevalence and timing of dementia in Lewy body diseases. (2nd December 2015) - Ruffmann, C.; Calboli, F. C. F.; Bravi, I.; Gveric, D.; Curry, L. K.; de Smith, A.; Pavlou, S.; Buxton, J. L.; Blakemore, A. I. F.; Takousis, P.; Molloy, S.; Piccini, P.; et al.
Abstract : Aims: Our main objective was to determine the neuropathological correlates of dementia in patients with Lewy body disease (LBD). Furthermore, we used data derived from clinical, neuropathological and genetic studies to investigate boundary issues between Dementia with Lewy bodies (DLB) and Parkinson's disease with (PDD) and without (PDND) dementia. Methods: One hundred and twenty‐one cases with a neuropathological diagnosis of LBD and clinical information on dementia status were included in the analysis (55 PDD, 17 DLB and 49 PDND). We carried out topographical and semi‐quantitative assessment of Lewy bodies (LB), Aβ plaques and tau‐positive neuropil threads (NT). The APOE genotype and MAPT haplotype status were also determined. Results: The cortical LB (CLB) burden was the only independent predictor of dementia (OR: 4.12, P < 0.001). The total cortical Aβ plaque burden was an independent predictor of a shorter latency to dementia from onset of motor signs ( P = 0.001). DLB cases had a higher LB burden in the parietal and temporal cortex, compared to PDD. Carrying at least one APOE ϵ4 allele was associated with a higher cortical LB burden ( P = 0.02), particularly in the neocortical frontal, parietal and temporal regions. Conclusions: High CLB burden is a key neuropathological substrate of dementia in LBD. Elevated cortical LB pathology and Aβ plaque deposition are both correlated with a faster progression to dementia. The higher CLB load in the temporal and parietal regions, which seems to be a distinguishing feature of DLB, may account for the shorter latency to dementia and could be mediated by the APOE ϵ4 allele. Abstract : Cortical Lewy body load is a neuropathological substrate of dementia in Lewy body diseases and cortical Lewy bodies and Aβ plaque burden both correlate with faster progression to dementia. A strong association of cortical Lewy body load and APOE ϵ4 allele suggests that this may modulate Lewy body pathology.